Psectrotanypus Kieffer (Diptera: Chironomidae: Tanypodinae) from China - Cheng, Ming; Wang, Xinhua H. (Zootaxa, 2006)
Adults of the genus Psectrotanypus are recorded from the Oriental Region for the first time. Psectrotanypus lateralis sp. n. is described and P. varius (Fabricius) is redescribed from males, and a key to males of the genus worldwide is presented.